The Vakkejokk Breccia: An Early Cambrian proximal impact ejecta layer in the North‐Swedish Caledonides. (6th March 2017) - Ormö, J.; Nielsen, A. T.; Alwmark, C.
Abstract: The ≤27 m thick Vakkejokk Breccia is intercalated in autochthon Lower Cambrian along the Caledonian front north of Lake Torneträsk, Lapland, Sweden. The spectacular breccia is here interpreted as a proximal ejecta layer associated with an impact crater, probably ~2–3 km in size, located below Caledonian overthrusts immediately north of the main breccia section. The impact would have taken place in a shallow‐marine environment ~520 Ma ago. The breccia comprises i) a strongly disturbed lower polymict subunit with occasional, in themselves brecciated, crystalline mega‐clasts locally exceeding 50 m surrounded by contorted sediments; ii) a middle, commonly normally graded, crystalline‐rich, polymict subunit, in turn locally overlain by iii) a thin fine‐grained quartz sandstone, <30 cm thick. The upper sandstone is sporadically either overlain, or replaced, by a conglomerate. In progressively more distal parts of the ejecta layer, the lower subunit is better described as only slightly disturbed strata. The lower subunit is suggested to have formed by ejecta bombardment of the strata surrounding the impact crater, even causing some net outwards mobilization of the sediments. The middle subunit and the uppermost quartz sandstone are considered resurge deposits. The top conglomerate may be caused by subsequent wave reworking and slumping of material from the elevated rim. Quartz grains showing planar deformation features are present in the graded polymict subunit and the upper sandstone, that is, the inferred resurge deposits.